The Islamic Council of Norway and the Challenge of Representing Islam in Europe: Muslims under Pressure - Elgvin, Olav (Muslim Minorities Series, 2025)
Governments all across Europe have attempted to govern the Muslim population by working with representative Muslim councils. These councils, however, have often been plagued by conflicts and splits. Through a detailed study of The Islamic Council of Norway, this book asks why